Cooperative Dehydrogenation of N‐Heterocycles Using a Carbon Nanotube–Rhodium Nanohybrid. Issue 19 (17th March 2015) - Jawale, Dhanaji V.; Gravel, Edmond; Shah, Nimesh; Dauvois, Vincent; Li, Haiyan; Namboothiri, Irishi N. N.; Doris, Eric
Abstract: Rhodium nanoparticles were anchored on carbon nanotubes and the resulting nanohybrid was studied as co‐catalyst, along with tert ‐butylcatechol, for the dehydrogenation of various N‐heterocycles. The co‐catalytic system operates in high yields, under the mildest conditions reported so far, and can be applied to a wide variety of secondary amine‐containing scaffolds. Abstract : Rhodium nanoparticles were anchored on carbon nanotubes and the resulting nanohybrid was studied as a co‐catalyst, along with tert ‐butylcatechol, for the dehydrogenation of N‐heterocycles.